2019
DOI: 10.1007/s12471-019-01306-y
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations of and management actions following electrocardiograms in symptomatic patients in primary care: a retrospective dossier study

Abstract: BackgroundThe electrocardiogram (ECG) has become a popular tool in primary care. The clinical value of the ECG depends on the appropriateness of the indication and the interpretation skills of the general practitioner (GP).ObjectivesTo describe the use of electrocardiography in primary care and to assess the performance of GPs in interpreting ECGs and making subsequent management decisions.MethodsThree hundred ECGs, recorded during daily practice in symptomatic patients by 14 GPs who regularly perform electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The overall reference send rate was 43.0%, which is an important cardiac condition property of the included patient population. This referral to cardiologist care rate is similar to that of other studies, confirmed by the literature, with a typical range of 30%–50% 17–20…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The overall reference send rate was 43.0%, which is an important cardiac condition property of the included patient population. This referral to cardiologist care rate is similar to that of other studies, confirmed by the literature, with a typical range of 30%–50% 17–20…”
Section: Resultssupporting
confidence: 89%
“…This referral to cardiologist care rate is similar to that of other studies, confirmed by the literature, with a typical range of 30%-50%. [17][18][19][20]…”
Section: Reference Referral Decisionmentioning
confidence: 99%
“… 20 , 21 This is supported by work where GPs’ interpretation of 12-lead ECG was compared with cardiologist or expert panel interpretation, where GPs struggled with diagnosing repolarization disorders but were highly accurate in AF detection. 22–24 Practice nurses felt less confident in diagnosing or ruling out AF than GPs. 20 The emergence and dissemination of single-lead devices has provided a new challenge in terms of independent ECG interpretation by GPs, as accuracy in diagnosing AF has so far been less accurate, 25 prompting the recommendation to have suspected positive AF single-lead ECG readings confirmed by a cardiologist.…”
Section: Screening and Detection Of Atrial Fibrillation: Current Prac...mentioning
confidence: 99%
“…Patients seem to appreciate the use of POCUS, 37,38 but questions remain regarding the reliability and diagnostic accuracy of a GP POCUS scan 30 and the challenges of evaluating and monitoring technology based in the community. 39,40 Until data is available for developing evidence-based guidelines 11 about appropriate and inappropriate POCUS use in general practice, interim experience-based recommendations based on basic ethical clinical principles, eg, primum non nocere (first, do no harm), may guide and encourage prudence among GPs (Figures 1-4).…”
Section: Qualitativementioning
confidence: 99%